A New Proton Conductive Liquid with No Ions: Pseudo‐Protic Ionic Liquids. Issue 35 (19th July 2013) - Doi, Hiroyuki; Song, Xuedan; Minofar, Babak; Kanzaki, Ryo; Takamuku, Toshiyuki; Umebayashi, Yasuhiro
<x xml:space="preserve">Abstract</x> Liquids with no ions! Raman analysis and quantum calculations suggest that electrically neutral molecular species predominantly exist in an N‐methylimidazole and acetic acid equimolar mixture, and that ionic species are rather minor. Nevertheless, the mixture has significant ionic conductivity, and shows "good ionic" or "superionic" behavior (see figure). It may be suitable to call such liquids "pseudo‐ionic liquids" rather than "ionic liquids".<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>